Exploring the link between cognitive processes and learning from refutational text. (29th March 2012) - McCrudden, Matthew T.; Kendeou, Panayiota; Kendeou, Panayiota
<x xml:space="preserve">Abstract</x> The purpose of this exploratory study was to investigate the cognitive processes used by individuals who read a refutational text about physics and demonstrated conceptual change learning. Four high school readers whose initial conceptions differed from the scientific conception of Newton's first law thought aloud while reading a refutational text. After reading, they completed a post‐test and participated in an in‐depth interview in which they were asked to provide interpretations of their think‐aloud comments. Qualitative analysis revealed that readers used a variety of cognitive processes during reading and their incorrect conceptions were revised to be more in line with the scientific conception explained in the text. The findings were consistent with the co‐activation hypothesis, which predicts that refutational texts can induce cognitive conflict and facilitate conceptual change learning.